IDENTIFIKASI LOGIKA-LOGIKA ARSITEKTUR BERKELANJUTAN DALAM PENELITIAN DAN PRAKTEK BERARSITEKTUR - Yanuarius Benny Kristiawan; Sidhi Pramudito (Jurnal Arsitektur ARCADE, 2022)
Abstract: Architecture is part of the overall process of the building and construction industry. The latest report by the World Green Building Council (WGBC) in 2019 states that buildings and construction are responsible for 39% of carbon emissions in the world. Therefore, the vision for 2050 needs to be supported by various research actions and their application in sustainability-related architecture. Simon Guy's writings about the practice of sustainable architecture that cannot be seen as a mere technological solution become the basis for inspiration on what types of research have been carried out. Architectural works analysis needs a more pluralistic view. Based on Simon Guy's research, a literature study using a rationalistic research paradigm with a quantitative deductive method was carried out. It is hoped that opportunities for design theme activities, research, and other activities with the theme of sustainable architecture can be identified. Based on the analysis of the six logics of sustainable architecture themes, there are still opportunities for studies in the eco-centric and eco-aesthetic fields. There is a finding that critical regional dimensions in sustainable architectural practice need to be clearly stated. At a more strategic level, the procurement of locally available materials and local development practices would be more profitable when considering the workforce's skills to reduce the negative impact of the ecological footprint on construction projects. The Socio-Cultural theme approach in solving energy problems and sustainable architecture is an essential issue in managing the future.Abstrak: Laporan terbaru World Green Building Council (WGBC) tahun 2019 menyebutkan bahwa bangunan dan konstruksi bertanggungjawab terhadap 39% emisi karbon di dunia. Visi untuk tahun 2050 perlu didukung dengan berbagai tindakan penelitian dan penerapannya dalam bidang arsitektur yang terkait dengan keberlanjutan. Tulisan Simon Guy tentang praktek arsitektur berkelanjutan yang tidak bisa dipandang sebagai pemecahan teknologi semata menjadi pijakan untuk menjadi inspirasi tentang jenis riset apa saja yang telah dilakukan. Pandangan yang lebih pluralistik dibutuhkan dalam menganalisis karya arsitektur. Penelitian studi pustaka ini berdasarkan tulisan Simon Guy yang menggunakan paradigma penelitian rasionalistik dengan metode deduktif kuantitatif. Diharapkan teridentifikasi peluang kegiatan bertema desain, penelitian dan kegiatan lain yang bertemakan arsitektur berkelanjutan. Berdasar analisis enam logika-logika tema arsitektur berkelanjutan, terbuka peluang yang lebih luas pada kajian-kajian bidang eco-centric dan eco aesthetic. Terdapat temuan bahwa dimensi regional yang penting dalam praktek arsitektur berkelanjutan harus dinyatakan dengan jelas. Pada tingkat yang lebih strategis pengadaaan bahan lokal yang tersedia dan praktek pembangunan daerah akan lebih menguntungkan apabila mempertimbangkan keterampilan tenaga kerja untuk mengurangi dampak negatif dari sisi jejak ekologis pada proyek konstruksi. Pendekatan tema Sosio-Kultural dalam menyelesaikan permasalahan energi dan arsitektur berkelanjutan menjadi isu penting dalam menata masa depan.